Identificação de siglas em textos - Mezzalira, Cezar Augusto (2015)
Academic papers (such as training report and research projects and extension, monographs and dissertations) generally have list of acronyms (composed by the initial letters of words and phrases), abbreviations (of the word) and acronyms (letters or initial syllables of expressions forming pronounceable words). These lists must contain all terms (acronyms, abbreviations) that kind that are contained in the text and their respective description. In the text, these kinds of terms must to be preceded, in the first occurrence, from your description. The location of the terms in the text and the description in the first occurrence is a laborious activity, especially if is a long text. Aiming to assist in this activity, an application was developed in order to identify the acronyms in the text, describe them on their first occurrence and generate a list of these terms with their descriptions. The developed application is to web ambience and was implemented using Java and Technologies associated with web development, such as Spring. The Apache POI was used in the implementation in one of the main features of the system, which is the identification of the terms in the text. For the query terms to identify the description, a database is used. The features to generate a list of acronyms and their description have been implemented in a preexisting application, developed with the aim of register acronyms and their meanings and enable the search of the acronyms, generating listings. The main restriction for the implemented work is that the only handled files are those in the .docx format.